Автоматизована система охоронної сигналізації для промислового підприємства - Кугір, А. В. (ХНУРЕ, 2021)
The GSM security alarm system, its components and the principle of operation are considered. In the course of the work, the advantages of GSMsignaling were identified and the disadvantages were identified, one of the reasons for which is the fact that some mobile operators do not support the use of such devices in their network. It is proposed to solve the shortcoming by developing a bot telegram that will be able to notify the user about security breaches.
Keywords: охоронна сигналізація; автоматизована система; промислові підприємства